Penilaian Fungsi Sosial Lanjut Usia Menggunakan Instrumen APGAR - Luhung, Monika; Dwi Astutik, Nanik (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Aging factors render the elderly less potent, capable, and more dependent on others' assistance. Increased dependency occurs due to physical, psychological, and social decline. The APGAR instrument (Adaptation, Partnership, Growth, Affection, Resolve) Objective: The objective of this community service activity is to enhance the understanding, knowledge, and skills of health cadres in assessing the social functions of the elderly using the APGAR Instrument. Method: Training for health cadres is conducted through material delivery methods and demonstrations of assessing the social functions of the elderly using the APGAR instrument. Cognitive success is evaluated through pre-and post-tests, while the skills of health cadres are assessed through the re-demonstration of APGAR assessment. Result: The results of the pre-test on social functions and the assessment of the social functions of the elderly showed that 11 individuals (61%) had sufficient understanding, 7 individuals (39%) had insufficient understanding, while in the post-test, 8 individuals (44%) had sufficient understanding, and 10 individuals (56%) had good understanding. The demonstration results showed that 14 individuals (77.8%) were able, and 4 individuals (22.2%) were sufficiently able to conduct social function assessments using the APGAR instrument. Conclusion: Based on the training results, it can be concluded that the understanding and knowledge of health cadres regarding social functions and the assessment of the social functions of the elderly mostly improved, and almost all of them were able to conduct assessments using the APGAR instrument.